2019
DOI: 10.1016/j.agrformet.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning evapotranspiration of a drip-irrigated wheat crop: Inter-comparing eddy covariance-, sap flow-, lysimeter- and FAO-based methods

Abstract: A precise estimate of the evapotranspiration (ET) partitioning is fundamental for determining the crop water needs and optimizing irrigation management. The plant transpiration (T) is generally considered to be the most desirable component, while reducing the soil evaporation (E) could be one of the most important water-saving actions in semi-arid agricultural regions. Given the lack of reference method to estimate the E/T partitioning of wheat crop, this study inter-compares four different methods based on ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 50 publications
3
36
0
1
Order By: Relevance
“…These findings of a sustained evaporation component and non-zero E/ET even during dry conditions were also supported by lysimeter measurements in a semiarid grassland (Moran et al, 2009) and partly confirmed by a recent study based on isotopes on shrubs and steppe ecosystem . The maximum daily T/ET found by Scanlon and Kustas (2012) in a maize agroecosystem was also about 0.8, but Rana et al (2018) found daily values that intermittently exceeded 0.9 in wheat and fava bean fields and multi-method comparisons suggest that T/ET 10 approaches 0.85 (Rafi et al, 2019). Anderson et al (2017a) found that T/ET routinely exceeded 0.9 in sugarcane, with maximum daily values above 0.95.…”
Section: Does T/et Approach Unity?mentioning
confidence: 96%
“…These findings of a sustained evaporation component and non-zero E/ET even during dry conditions were also supported by lysimeter measurements in a semiarid grassland (Moran et al, 2009) and partly confirmed by a recent study based on isotopes on shrubs and steppe ecosystem . The maximum daily T/ET found by Scanlon and Kustas (2012) in a maize agroecosystem was also about 0.8, but Rana et al (2018) found daily values that intermittently exceeded 0.9 in wheat and fava bean fields and multi-method comparisons suggest that T/ET 10 approaches 0.85 (Rafi et al, 2019). Anderson et al (2017a) found that T/ET routinely exceeded 0.9 in sugarcane, with maximum daily values above 0.95.…”
Section: Does T/et Approach Unity?mentioning
confidence: 96%
“…These findings of a sustained evaporation component and nonzero E/ET even during dry conditions were also supported by lysimeter measurements in a semiarid grassland (Moran et al, 2009) and partly confirmed by a recent study based on isotopes in shrubs and a steppe ecosystem . The maximum daily T / ET found by Scanlon and Kustas (2012) in a maize agroecosystem was also about 0.8, but Rana et al (2018) found daily values that intermittently exceeded 0.9 in wheat and fava bean fields, and multi-method comparisons suggest that T / ET often approaches 0.85 (Rafi et al, 2019). Anderson et al (2017a) found that T / ET routinely exceeded 0.9 in sugarcane, with maximum daily values above 0.95, and Li et al (2019) also found values greater than 0.9 for other crops.…”
Section: Does T / Et Approach Unity?mentioning
confidence: 97%
“…As a consequence, the spatial modeling has become a dominant means of estimating ET fluxes over regional and continental areas (Anderson et al, 2007;Fisher et al, 2017). In this context, numerous models based on land surface temperature (LST) data have been developed, such as (i) residual balance methods that consider ET to be the residual term of the energy balance, like TSEB (two-source energy balance, and SEBS (surface energy balance system, Su, 2002), (ii) contextual methods that estimate ET as the potential ET times the evaporative efficiency (Moran et al, 1994) or as the available energy times the evaporative fraction (Merlin et al, 2013;Roerink et al, 2000) and (iii) other categories of models that integrate LST into a water balance model or into the Penman-Monteith energy balance (PMEB) equation to directly estimate ET Mallick et al, 2015Mallick et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%